The adventure of the human intellect : self, society, and the divine in ancient world cultures - Raaflaub, Kurt A. (Chichester, West Sussex, UK : Wiley Blackwell, 2016)
The Adventure of the Human Intellect presents the latest scholarship on the beginnings of intellectual history on a broad scope, encompassing ten eminent ancient or early civilizations from both the Old and New Worlds. -Borrows themes from The Intellectual Adventure of Ancient Man (1946), updating an old topic with a new approach and up-to-date theoretical underpinning, evidence, and scholarship -Provides a broad scope of studies, including discussion of highly developed ancient or early civilizations in China, India, West Asia, the Mediterranean, and the Americas -Examines the world view of ten ancient or early societies, reconstructed from their own texts, concerning the place of human beings in society and state, in nature and cosmos, in space and time, in life and death, and in relation to those in power and the world of the divine -Considers a diversity of sources representing a wide array of particular responses to differing environments, circumstances, and intellectual challenges -Reflects a more inclusive and nuanced historiographical attitude with respect to non-elites, gender, and local variations -Brings together leading specialists in the field, and is edited by an internationally renowned scholar.
Introduction / Francesca Rochberg, Kurt A Raaflaub -- A Critique of the Cognitive-historical Thesis of / Francesca Rochberg -- The Intellectual Adventure of Ancient Man / Peter Machinist -- The World of Ancient Egyptian Thought / James P Allen -- On Speculative Thought in Ancient Mesopotamia / Benjamin R Foster -- Self, Substance, and Social Metaphysics / Ryan Byrne -- Ancient Greece / Kurt A Raaflaub -- The Thought-World of Ancient Rome / Robert A Kaster, David Konstan -- Self, Cosmos, and Agency in Early China / Lisa Raphals -- Vedic India / Stephanie W Jamison --'Chronosophy' in Classic Maya Thought / Stephen Houston -- The Word, Sacrifice, and Divination / Guilhem Olivier -- Night Thoughts and Spiritual Adventures / Peter Nabokov.
Includes index.
Print version record.
Keywords: Philosophy, Ancient; Intellect -- History; Intellectual life -- History; Self -- History; Thought and thinking -- History; Electronic books; History